Peran Etika dan Moral dalam Membangun Akhlak Siswa-Siswi SD Banjaragung III Bareng Jombang - Susilo, Dwi Ermayanti; Chasanah, Ina Nikmatul; Supriyadi, Andhi; Purba, Darwin Marasi; Rusmawan, Teddy (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Moral education in schools needs to be carried out seriously to build a quality generation of the nation. Although the main role in educating children's morals is the role of parents, teachers in schools also play a big role in realizing the morals students should have. Families, schools and communities are also responsible for educating the younger generation to have good morals and intellectual intelligence so that a superior young generation can be created. The development of ethics and morals in schools is also very important for every teacher to pay attention to, considering that this is where students begin to become familiar with various fields of scientific study. During this period, students also begin to realize their identity as human beings who begin to grow with the various problems that accompany it. Method: The method used in this community service goes through several stages, namely: location survey, coordination of time, place and implementation, as well as delivery of ethical and moral material. Armed with noble moral values obtained through the learning process in the classroom and outside the classroom, students are expected to become human beings with character and knowledge who are ready to be developed at a higher level of education. Because everyone definitely has goals in life, whether short-term, medium-term or long-term goals. Conclusion: Moral education in schools must also be designed to cover various aspects, namely: educators, materials, methods and evaluation so that the results are expected to be optimal.